## Solving the Equation: (x+2)+2=10(x−2)+2x

This article will guide you through solving the equation **(x+2)+2=10(x−2)+2x**. We will use the principles of algebra to isolate the variable "x" and find its value.

### Step 1: Simplify both sides of the equation.

**Left side:**(x+2)+2 can be simplified to**x+4****Right side:**10(x−2)+2x can be expanded to**10x - 20 + 2x**, which further simplifies to**12x - 20**

Our equation now looks like this: **x + 4 = 12x - 20**

### Step 2: Combine like terms.

**Subtract x from both sides:**4 = 11x - 20**Add 20 to both sides:**24 = 11x

### Step 3: Isolate x.

**Divide both sides by 11:**x = 24/11

### Solution

Therefore, the solution to the equation (x+2)+2=10(x−2)+2x is **x = 24/11**.

This can be verified by substituting the value of x back into the original equation and confirming that both sides are equal.